The cardiovascular, metabolic, fetal and neonatal effects of CPAP use in pregnant women: a systematic review - Migueis, Debora Petrungaro; Urel, Arthur; Santos, Camila Curado dos; Accetta, Andre; Burla, Marcelo (Sleep Science, 2022)
Continuous positive airway pressure (CPAP) is the standard treatment for obstructive sleep apnea (OSA), but its outcomes for the pregnant are still undefined. This study aims to review current CPAP intervention during pregnancy, discuss published trials, and propose relevant issues that have yet to be addressed satisfactorily about the cardiovascular, metabolic, fetal, and neonatal effects of CPAP treatment during gestation. Two authors independently conducted a systematic review until March 28th, 2021 on PubMed, BVS, and Cochrane Library, using PRISMA guidelines, and risk of bias. Discrepancies were reconciled by a third reviewer. Of 59 identified citations, eight original trials have submitted a total of 90 pregnant women to polysomnography and CPAP therapy. Four studies performed in samples with hypertension or preeclampsia presented blood pressure decrease or maintained the antihypertensive drug dose in the CPAP group. After CPAP utilization, one trial registered cardiac output and stroke volume increase with heart rate and peripheral vascular resistance decrease, which were correlated with birth weight increment. Others documented a higher Apgar in the CPAP group and more fetal movements during CPAP use. There was a reduction in serum uric acid and tumor necrosis factor-alpha in the CPAP groups whose blood pressure decreased. However, two weeks of CPAP use in women with gestational diabetes and OSA did not improve glucose levels but raised the insulin secretion in those adherents to CPAP. Despite these positive results without adverse effects, randomized controlled trials with standardized follow-up in larger populations are required to determine CPAP therapy recommendations in pregnancy.
Keywords: Continuous Positive Airway Pressure; Obstructive Sleep Apnea; Gestational Diabetes. Preeclampsia; Pregnancy; Hypertension; Pregnancy-Induced